Characteristics and communication skills of health professionals in implementing provider-initiated HIV testing and counselling (PITC) for Indonesian pregnant women - Hikmah, Faiqatul; Notobroto, Hari Basuki; Devy, Shrimarti Rukmini; Triyono, Erwin Astha (Pharmacy Education, 2023)
Background: HIV testing for pregnant women is an important test during pregnancy. HIV testing for pregnant women is a way to prevent mother-to-child HIV transmission. Objectives: To investigate the relationship between the characteristics and communication skills of health professionals while conducting provider-initiated HIV testing and counselling (PITC) for pregnant women. Methods: This was an observational study with a cross-sectional approach. The study was conducted at 23 public health centres with 80 health professionals who conduct PITC. The data was analysed using the Chi-Square test. Results: There was a correlation between the characteristics and communication skills of respondents. Relationships were observed between respondents trained on PITC and communication with patients during PITC sessions (p=0.002); work experience and non-verbal communication skills (p=0.047), and type of profession of respondents and non-verbal communication skills (p=0.029). Conclusions: Communication skills had a relationship with experienced training on PITC, work experience, and type of profession. Increasing the communication skill of health professionals through work experience and training or education to improve the ability of health professionals in PITC services.